Internal splinting of dorsal intertarsal and tarsometatarsal instabilities in dogs and cats with the ComPact UniLock 2.0/2.4TM System - Voss, K.; Keller, M.; Montavon, P. M. (Veterinary and Comparative Orthopaedics and Traumatology, 2004)
Dorsal intertarsal and tarsometatarsal instabilities are considered to be uncommon in dogs and only a few cases have been reported in cats. Treatment usually consists at partial arthrodesis. Internal splinting of the affected joints represents an alternative surgical method, with the goal of preserving joint function. In the present study, 13 animals (10 cats and 3 dogs) with dorsal, dorsomedial or dorsolateral intertarsal or tarsometatarsal instabilities, treated with an internal fixator (ComPact UniLock 2.0/2.4™ System) in bridging function, were reviewed. The joint cartilage was left intact. Follow-up time ranged from one month to one year postoperatively. The clinical outcome was considered good or excellent in 12 of the animals and moderate in one cat. The implants were removed from three patients. Follow-up radiographs were available for 10 cases. Joint space narrowing, or joint fusion, occurred in three cases. A broken screw each in one cat and one dog did not affect the stability of the joints involved. The technique described is simple and less invasive than partial arthrodesis and results suggest it as being a valuable alternative to partial arthrodesis. Early implant removal might possibly prevent cartilage damage and joint fusion due to prolonged immobilization.
Keywords: Tarsus; dorsal instability; internal fixator